Editorial Revista Porto Arte n º 38 ano 2018 - Barachini, Teresinha; Carvalho, Ana Maria Albani de; Corona, Marilice Villeroy; Zielinsky, Monica; Silveira, Paulo Antonio (PORTO ARTE: Revista de Artes Visuais, 2018)
.